Pengaruh Jus Pepaya Terhadap Tekanan Darah Pada Menopause Penderita Hipertensi di Posbindu Puskesmas Karangapwitan Kabupaten Garut Tahun 2024 - Yunita, Ita; Wulandari, Ratna; Prima, Ernita (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Karangpawitan Health Center in 2023 was the largest population that experienced referrals and there was an increase from the previous year, which was 36% to 37.4%, so that various factors can affect the occurrence of hypertension, especially in the elderly. One alternative non-pharmacological treatment for hypertension patients is giving 200 grams of ripe papaya. Mineral content, ripe papaya has a potassium content of 257 mg/100 g and very little sodium content. The high incidence of hypertension needs to be prevented because hypertension can cause death. The purpose of this study was to determine the effect of papaya juice on blood pressure in menopause with hypertension. This research method uses a quasi-experimental with a pretest-posttest one group design. The population in this study were all pregnant women who underwent examinations and were diagnosed with hypertension as many as 36 people, the sample technique used total sampling with a sample size of 36 respondents. The instruments used were equipment to measure blood pressure and a set of tools to record the results. Data analysis used a one-group t-test. The results of the study showed that the average systolic blood pressure before being given chayote was 145.44 and diastolic was 93.89, while after being given papaya juice it was 134.83 and diastolic was 87.50. The bivariate results showed p = 0.000. There is a significant effect of giving papaya juice on hypertension in menopausal women. It is recommended for menopausal women to increase their knowledge about how to lower blood pressure during pregnancy, one of which is by non-pharmacological means by consuming papaya juice either in the form of juice or however it is according to taste, the important thing is in a safe dose